Daclatasvir: potential role in hepatitis C - Lee C (Dove Medical Press, 2013)
Choongho Lee College of Pharmacy, Dongguk University-Seoul, Goyang, Republic of Korea  Abstract: Chronic hepatitis C virus (HCV) infection is responsible for the development of liver cirrhosis and hepatocellular carcinoma. It has been a tremendous burden on global health care systems. With the advent of a number of new direct-acting and host-targeting antiviral agents, current interferon-α- and ribavirin-based HCV therapy has started to move towards an interferon-sparing or even interferon-free strategy. In this regard, a recently identified NS5A inhibitor, daclatasvir, showed a great promise in clinical trials as another new class of direct-acting anti-HCV therapeutics, with a distinct mechanism of action. In this review, a variety of preclinical as well as clinical proof-of-concept studies of daclatasvir, including the studies of its discovery, mechanism of action, viral resistance, and host polymorphism profiles are reviewed. In addition, a role of daclatasvir in the future therapy for HCV patients is discussed briefly. Keywords: hepatitis C virus, nonstructural protein 5A, NS5A inhibitor, hepatitis C treatment